2012
DOI: 10.1210/en.2011-1949
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Novel Reproductive Defects in Neurokinin B Receptor Null Mice: Closing the Gap Between Mice and Men

Abstract: Patients bearing mutations in TAC3 and TACR3 (which encode neurokinin B and its receptor, respectively) have sexual infantilism and infertility due to GnRH deficiency. In contrast, Tacr3(-/-) mice have previously been reported to be fertile. Because of this apparent phenotypic discordance between mice and men bearing disabling mutations in Tacr3/TACR3, Tacr3 null mice were phenotyped with close attention to pubertal development, estrous cyclicity, and fertility. Tacr3(-/-) mice demonstrated normal timing of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 59 publications
7
76
0
1
Order By: Relevance
“…found to coexpress another neuromodulator implicated in the regulation of gonadotrope axis, neurokinin B (16,17). Thus, we also measured Tac2 gene and protein (NKB) expression, which was not altered after PRL administration ( Figure 2F and Supplemental Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…found to coexpress another neuromodulator implicated in the regulation of gonadotrope axis, neurokinin B (16,17). Thus, we also measured Tac2 gene and protein (NKB) expression, which was not altered after PRL administration ( Figure 2F and Supplemental Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…The translational relevance of such coexpression, and of NKB actions in the reproductive brain, is reinforced by data from human studies that demonstrated that lossof-function mutations in the genes encoding either NKB (TAC3 in humans) or its receptor, NK3R (TAC3R in humans), are associated with impuberism and iHH (29,30,31), a phenotype similar to that of GPR54 or KISS1 null humans (10). Yet, NK3R null mice appear to display normal pubertal timing in males and females (32). To add further complexity, dynorphin-A (Dyn) and NK3R have also been found in Kiss1/NKB expressing neurons (25); Kiss1/NKB/Dyn colocalization being a specific feature of the ARC/infundibular population of Kiss1 neurons, which has been renamed as KNDy to emphasize the potential usage of these three neuropeptides (23).…”
Section: Kisspeptins: Major Gatekeepers Of Pubertymentioning
confidence: 99%
“…In a human sample of 209 patients who all exhibited cognitive impairments, we found that the r2765 SNP in the TACR3 gene predicted the degree of learning and memory impairment in two neuropsychological tests of word-list learning. Mutations in the human TACR3 gene have been shown to play an important role in puberty development and are associated with hypogonadotrophic hypogonadism (40). An association with cognitive performance has also been suggested by animal studies using NK3-R knockout mice (15).…”
Section: Discussionmentioning
confidence: 99%